2017
DOI: 10.1093/protein/gzx001
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the expression of an anti-interleukin-13 antibody through rational design and mutagenesis

Abstract: High levels of protein expression are key to the successful development and manufacture of a therapeutic antibody. Here, we describe two related antibodies, Ab001 and Ab008, where Ab001 shows a markedly lower level of expression relative to Ab008 when stably expressed in Chinese hamster ovary cells. We use single-gene expression vectors and structural analysis to show that the reduced titer is associated with the VL CDR2 of Ab001. We adopted two approaches to improve the expression of Ab001. First, we used mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…For example, they will not detect sources of immunogenicity, nor more subtle mechanisms that lead to poor stability. Nevertheless, we have shown that the TAP guidelines can selectively highlight antibodies with expression or aggregation issues (11,34). The choice of 5 th /95 th percentile amber flag cut-offs proved useful in distinguishing weak aggregators from non-aggregators ( Fig.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…For example, they will not detect sources of immunogenicity, nor more subtle mechanisms that lead to poor stability. Nevertheless, we have shown that the TAP guidelines can selectively highlight antibodies with expression or aggregation issues (11,34). The choice of 5 th /95 th percentile amber flag cut-offs proved useful in distinguishing weak aggregators from non-aggregators ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…4B), again red-flagging the candidate with prohibitive developability issues. Both AB001 and AB008, confirmed monomers in solution (11), did not flag for CDR vicinity PSH score (Fig. 4A).…”
Section: R a F Tmentioning
confidence: 92%
See 3 more Smart Citations